Public Administration 4.0 : Theoretical Exploration of Disruptive Governance Paradigm - Ahmad Syakrani Bunasim (Indonesian Association for Public Administration (IAPA), 2020)
For a long time, public sector was trapped in a false belief; a myth that it did not need to change, that it did not need to be strong, wiser, agile, dynamic, and adaptive to an everchanging environment as it became an inevitable factor for corporations, who had to maintain their competitive advantage in order to always to be more excellent than other corporations. This paper will trace that in the era of Fourth Industrial Revolution, the public sector has to earnestly get out of this trap and need to inject new DNA; not only entrepreneurship DNA, but also disruptive governance DNA that inducts on innovative disruption, agility, and dynamic governance so that it will not only carry out the routinized governance responsibilities, but it can also be present in the middle of the public with strong, wiser, agile, adaptive, and humane presence. This paper concludes with an offer of a model of disruptive governance that is the core of Public Administration 4.0.